Evolving indications and reported complications suggest total knee arthroplasty after acute and complex periarticular fractures remains a high-risk operation: a systematic review. Issue 5 (16th July 2019) - Lau, Simon; Guest, Catherine; Annabell, Lucas
Abstract : Importance: Complex periarticular fractures of the knee can be difficult to reconstruct with osteosynthesis, can result in poor function and can lead to increased morbidity and mortality—particularly in the elderly. Primary acute total knee arthroplasty (TKA) is a surgical option which is rarely performed, but thought to have high rates of complication postoperatively. Objective: To investigate the literature regarding optimal patient selection for TKA after acute fracture with particular emphasis on postoperative outcomes and complications. Evidence review: A literature search of the MEDLINE, EMBASE and Cochrane Databases using established methodology for conducting systematic reviews investigating acute TKA after trauma. Two reviewers screened citations using the methodological index for non-randomi zed studies score to determine inclusion, methodological quality assessment and data extraction. Findings: Eighteen papers met the inclusion criteria; totalling 284 acute arthroplasty procedures. The majority of cases were performed in elderly females and the most common fracture pattern was the Arbeitsgemeinschaft für Osteosynthesefragen type C. Inclusion criteria for acute arthroplasty—whether fracture or patient specific—was poorly defined. Modular, stemmed and highly constrained (condylar or hinged) prostheses were used. Complications were often seen including 44 deaths within 5 years of surgery and three instances of above knee amputation. Conclusion and relevance: Acute knee arthroplasty can be considered as primary management for an acute periarticular fracture in some cases, although patient selection is vital. These patients should also be viewed similar to fractured neck of femur patients and cared for appropriately. Level of evidence: 4.